Effects and affects of literature of Kuching secondary school students - Mohamad Tuah, Ahmed Shamsul Bahri (Kota Samarahan : Universiti Malaysia Sarawak, 2007., 2006)
The main rationale for teaching literature to secondary school students is for aesthetic purposes: understanding and appreciating literacy works by both local and international writers. This study focussed on the effects and affects of literature teaching on secondary school students in the Kuching region. A sample of 237 Form Five students from five urban secondary schools participated in the study. The questionnaire, created based on the literature aspects of Form Five English syllabus, consisted of items on students' reactions towards the teaching of literature, both cognitively and emotionally. The analysis of the students' questionnaire responses revealed that the students have fairly positive reactions towards the teaching of literature in school. They reported understanding a majority of the texts used and that they were able to gain new information and experience through the texts. In addition, they were also able to identify with both the characters and settings in the literary works. The students claimed that they learned good values and were able to relate what they learnt to their daily lives. However, when it came to retelling and reciting, and discussion and dramatisation, the students were less enthusiastic and less confident. More effective methods of implementation need to be formulated to better realise the philosophy of the Education Ministry where the teaching of literature is concerned and yet, as long as the Malaysian education system remains examination oriented, it will be a challenge to do so.